COVID-19 immunisation practices and religious-related hesitation : COVID-19 and religious-related hesitation - Ciliberti, Rosagemma; Siri, Anna; Petralia, Paolo; Bonsignore, Alessandro (Medicina Historica, 2021)
Several vaccines to fight the COVID-19 pandemic have been licensed or approved for human use, and many more are in advanced stages of clinical development. Herd immunity is the key to a quicker exit from a health emergency. However, increasing numbers of vaccine refusals may reduce coverage rates and threaten existing herd immunity, exposing those who have not or cannot be vaccinated to dangerous diseases.Even so, vaccination has long been the topic of various ethical controversies, moral considerations, concerns or restrictions regarding vaccination in general, the research design process, or specific vaccine ingredients.This article highlights the main issues of moral concern about vaccines and summarizes the recommendations on new vaccines by religious authorities.Knowing the results of the ethical-moral debates of different religious communities can help explain the importance and necessity of vaccines and improve communication between science and the community.